Evaluation outcomes of an alcohol and pregnancy campaign targeting multiple audiences. (6th September 2022) - Pettigrew, Simone; Booth, Leon; McCausland, Tahnee; Kennington, Kelly; Miller, Mia; Bowden, Jacqueline; Stafford, Julia
Abstract: Introduction: The aim of this study was to evaluate the effectiveness of a mass media campaign alerting the public to the potential harms of alcohol to unborn babies and to inform future intervention efforts. Method: An online survey was administered to 889 adult Western Australians. The survey assessed demographic characteristics, typical alcohol use, recognition and perceptions of the campaign, and behavioural changes resulting from campaign exposure. A multiple regression analysis was conducted to identify factors associated with perceived campaign effectiveness. Results: Most respondents reported having seen/heard the campaign on at least one form of media (71%). Most considered the campaign to be believable (89%), clear (88%), trustworthy (87%), memorable (82%) and among the best they had seen (78%). As a result of campaign exposure, a large majority reported increased concern about drinking during pregnancy (85%) and most female respondents reported being much less likely to use alcohol during a pregnancy (83%). One‐third of female respondents (33%) reported that as a result of being exposed to the campaign they had decided not to consume alcohol while pregnant. Confidence to abstain, awareness of strategies to abstain, lower socioeconomic position, residing in the metropolitan area and recognising the campaign were significantly associated with greater perceived campaign effectiveness. Discussion and Conclusions: Results indicate the campaign was well received by respondents, increased concern about drinking alcohol during pregnancy and positively influenced women's intentions to refrain from drinking while pregnant. Well‐designed campaigns on alcohol avoidance during pregnancy can be considered acceptable and effective by target audiences.